Maximizing Nutrient Availability for the Breastfed Infant Through Colonization with B. Infantis EVC001 (FS04-04-19). (13th June 2019) - Shafizadeh, Tracy; Frese, Steve; Casaburi, Giorgio
Abstract: Objectives: Human breastmilk contains complete nutrient composition required for the developing infant, including human milk oligosaccharides (HMO). These complex carbohydrates are indigestible by the infant alone, and require digestion by gut microbes, namely Bifidobacterium longum subsp . infantis (B. infantis) . However, decades of C-section delivery, formula feeding and increasing exposure to antibiotics have contributed the loss of this critical infant-associated gut bacterium in developed countries. Therefore, restoring B. infantis to the infant gut was hypothesized to improve the nutritional utilization of human breastmilk in healthy term infants. Methods: In an open trial, healthy, exclusively breastfed term infants were fed 1.8 × 10 10 CFU B. infantis EVC001 daily from day 7–27 postnatal (n = 34; EVC001-fed), or breastmilk alone (n = 32; control group). Fecal samples, milk samples, and weekly self-reported data were collected and analyzed for infant gut microbiome composition and function, human milk oligosaccharide composition, and fecal metabolites. 16S rRNA sequencing and shotgun metagenome sequencing provided characterization of microbial communities from birth through 60 days postnatal. Results: Infants fed B. infantis EVC001 were uniformly colonized with this organism at 10 11 CFU/g feces, while infants in the control group had a median total Bifidobacterium level below 10^5 CFU/g feces, despite exclusive breastfeeding. Mass spectrometry of fecal samples from B. infantis EVC001-fed infants showed that the resulting microbial community produced higher concentrations of lactate and acetate and lower excretion of HMO, while control infants showed significantly lower ability to capture and utilize these carbohydrates from human milk. Importantly, HMO content of breastmilk was not significantly different between groups and no difference was found in the gut microbiome of infants based on secretor status of mothers (presence or absence of 2'FL in breastmilk). Further, these changes were associated with reductions in taxa that have been associated with negative health outcomes including colic, asthma, eczema and allergy. Conclusions: Overall, colonization with B. infantis is observed to be an effective way to restore maximal function of the infant gut microbiome to improve nutrient availability in the breastfed infant. Funding Sources: This study was funded by Evolve BioSystems, Inc.